Book Reviews (Rev. Anal. Numér. Théor. Approx., 2009)
Book reviews for:Nicholas J. Higham, Handbook of Writing for the Mathematical Sciences, Second Ed., Philadelphia, 1998, ISBN 0-89871-420-6, XV + 302 pp. Reviewed by E. Catinas.L. Hodges, Jr. and E. L. Lehmann, Basic concepts of probability and statistics, Second Edition,  SIAM,  Philadelphia,  PA,  2005,  ISBN  0-89871-575-X,  XX  +  441  pp., Classics  in Applied Mathematics, 48. Reviewed by E. Catinas.Thomas W. O’Gorman, Applied  adaptive  statistical  methods.   Tests  of  significance  and confidence intervals, ASA, Alexandria, Virginia and SIAM, Philadelphia, Pennsylvania, 2004, ISBN 0-898715-53-9, XIII + 174 pp. Reviewed by E. Catinas.R. Peck, L.D. Haugh, A. Goodman, Statistical  case  studies.   A  collaboration  between Academe  and  Industry, ASA, Alexandria, Virginia, and SIAM, Philadelphia, Pennsylvania, 1998, ISBN 0-89871-413-3, XXXI + 282 pp. Reviewed by E. Catinas.Jenny A. Baglivo, Mathematica laboratories for mathematical statistics.  Emphasizing simulation and computer extensive methods, SIAM, Philadelphia, PA, 2005, ISBN 0-89871-566-0, XX + 260 pp. Reviewed by E. Catinas.John C. Strikwerda, Finite Difference Schemes and Partial Differential Equations, SIAM, Philadelphia, PA, 2004, ISBN 0-89871-567-9, XII + 434 pp. Reviewed by C. Revnic.